Comparação de respostas cinéticas, cinemáticas e de desempenho entre escaladores intermediários e avançados em diferentes ações musculares e a influência da resistência externa no pico de potência muscular no campus board. - Edgardo Alvares de Campos Abreu (2023)
The objectives of Study 1 were to compare the impulse, peak power, peak force, peak velocity, maximum reach, and vertical displacement of the center of mass between intermediate and advanced climbers, as well as between the BoteCon and BoteCAE exercises performed on the campus board (CB). The study also aimed to investigate the association and agreement of peak velocity measured using the impulse-momentum method and kinematics. In Study 2, the goal was to compare peak power produced using different external resistances (0%, 5%, 10%, 20%, and 30% of 1RM) in the BoteCon and BoteCAE exercises among advanced climbers. Study 1 included intermediate climbers (GroupINTER; N=10) and advanced climbers (GroupAVAN N=10). Study 2 included only advanced climbers (N=17). The procedures were carried out on two separate days (familiarization and data collection) with a 48- hour interval. After a standard warm-up, the 1RM test and maximum reach on the CB were performed for BoteCon and BoteCAE. In Study 2, five minutes after determining the maximum reach for one of the exercises, the participants performed the exercise with 0% (body weight only), 5%, 10%, 20%, and 30% of their 1RM. Kinetic analysis was conducted using the CB, which was instrumented with two load cells with a maximum capacity of 2,000N, properly calibrated, and a sampling rate of 1KHz. A low-pass filter of 10Hz was applied. The acquisition and processing of the analog signal were performed using the MATLAB© program. For kinematic analysis, two GoPro® cameras, model 7, were used in linear mode, with an acquisition frequency of 120 frames per second. The range of motion and angular velocity of the hip and knee, as well as the vertical linear velocity of the L5, were recorded using the Kinovea© program. Statistical assumptions were tested, and the measurement reliability was verified using the CCI(2.1) and EPM methods. In Study 1, a two-way mixed ANOVA was conducted for the factors group x exercise, and Cohen's d effect size was calculated. Spearman's correlation and Bland-Altman plots were also used. In Study 2, a repeated-measures ANOVA and Bonferroni post hoc test were used to determine the impact of external resistance, and Partial Eta Squared effect size was calculated. All statistical analyses were performed using the R© program. The adopted significance level was 5%. The results of Study 1 for impulse did not indicate interaction (F(1,18) = 0.776; p = 0.390; ηp² = 0.041). The main effect of group was statistically significant (F(1,18) = 22.9; p < 0.001; ηp² = 0.560), and similar results were found for all variables except for peak force, which indicated significant interaction (F(1,18) = 4.548, p = 0.047; ηp² = 0.202). The correlation was strong (rho = 0.78; p < 0.001), and the agreement was within acceptable limits (bias: -0.23; 95% CI: 0.59 to 0.95). In Study 2, peak power differed between external resistances (F(2,44) = 5.985; p = 0.002; ηp² = 0.272) and also between BoteCAE (F(2,32) = 8.496; p = 0.001; ηp² = 0.347). Conclusion of Study 1: Advanced climbers exhibit greater impulse, peak power, peak velocity, displacement, and maximum reach than intermediate climbers, and this behavior was not influenced by the type of muscle action. Conclusion of the Study 2 is that the peak power was statistically lower in the conditions of external resistances at 0%, 5%, 10%, and 20% of 1RM compared to the 30% of 1RM condition, both in the BoteCon and BoteCAE exercises.